First fossil representative of Cerylonidae (Coleoptera: Coccinelloidea) described using X-ray micro-computed tomography, from Eocene Baltic amber - Bukejs, Andris; Ślipiński, Adam; Mitchell, Jerit L.; Mckellar, Ryan C.; Barbi, Mauricio; Larsson, Hans C.e.; Alekseev, Vitalii I. (Zootaxa, 2021)
Based on material originating from five amber collections of Eocene Baltic amber, Protostomopsis pandema gen. et sp. nov. is described and illustrated using X-ray micro-computed tomography. It is the first formally described extinct species of Cerylonidae, and the first known Palaearctic representative of the subfamily Ostomopsinae. As such, the new species extends the temporal range of the family Cerylonidae by approximately 45 Ma.